2018
DOI: 10.4291/wjgp.v9.i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Enterobacteriaceae in the colon mucosa in diverticular disease

Abstract: AIMTo compare gut bacterial diversity and amount of Enterobacteriaceae in colonic mucosa between patients with and without diverticular disease (DD).METHODSPatients in a stable clinical condition with planned elective colonoscopy were included. Blood samples and colon mucosa biopsies were collected at the colonoscopy. Study questionnaires including questions about gastrointestinal symptoms were completed by the patients and physicians. DNA from mucosa samples was isolated and the amount of Enterobacteriaceae w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 36 publications
0
37
0
2
Order By: Relevance
“…Several animal studies have shown that a low-fibre diet substantially increases the rates for colonic diverticula [36][37][38][39]. Some studies have suggested differences in the gut microbiota of diverticular disease patients compared to controls [40][41][42][43][44][45] and one study suggested that patients with diverticular disease have depletion of microbiota with anti-inflammatory activity [40]. Further studies are needed to clarify whether and how fibre intake might interact with the microbiota in reducing diverticular disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have shown that a low-fibre diet substantially increases the rates for colonic diverticula [36][37][38][39]. Some studies have suggested differences in the gut microbiota of diverticular disease patients compared to controls [40][41][42][43][44][45] and one study suggested that patients with diverticular disease have depletion of microbiota with anti-inflammatory activity [40]. Further studies are needed to clarify whether and how fibre intake might interact with the microbiota in reducing diverticular disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Among Enterobacteriaceae family, Escherichia coli is the most common cause of diarrhea in pigs and piglets [22][23][24]. Research has shown that animals with signs of intestinal disease have far greater numbers of Enterobacteriaceae than do healthy individuals, and that the Enterobacteriaceae are linked to intestinal disorders [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…One example of an adverse effect of commonplace E. coli, is that early colonisation in infants increases the risk for atopic eczema later in life (Penders et al, 2007), and the same effect has low diversity, early in life (Abrahamsson et al, 2012;Ismail et al, 2012;Wang et al, 2008). It has also been observed that Enterobacteriaceae are abundant in the colonic mucosa of patients suffering from diverticular disease (Linninge et al, 2018). A clinically problem of considerable magnitude involving E. coli is urinary tract infections (UTIs) where it has been seen that uropathogenic E. coli often dominates the faecal microbiota of the…”
Section: Introductionmentioning
confidence: 99%